Efficient generation of human induced pluripotent stem cells from urine samples of patients with Fragile X syndrome - Dionne, Olivier; Sabatié, Salomé; Fortin, Fléchère; Corbin, François; Laurent, Benoit (Frontiers in Cell and Developmental Biology, 2024)
Human induced pluripotent stem cells (iPSCs) are a valuable tool for studying human development and diseases. iPSCs can be generated by reprogramming from any somatic cells, however establishing primary cell cultures can involve invasive procedures (e.g., skin biopsy) and be labor-intensive. In this paper, we describe an efficient, reliable, and non-invasive method for cultivating primary urine-derived cells (UDCs) and efficiently reprogram them into iPSCs using a feeder-free and non-integrative system. This approach has several advantages: (i) UDCs collection and culture are non-invasive, straightforward, and do not require medical personnel; (ii) reprogramming UDCs using commercially available Sendai viruses is highly efficient and reliable; and (iii) iPSCs generated from UDCs demonstrate strong differentiation potential. To showcase the effectiveness of this method, we generated iPSC lines from UDCs of three control individuals and three patients with Fragile X syndrome.